Moderating role of business support among internal challenges and firm performance of SMEs in Saudi Arabia - N Alfaqiri, Maryam Yousef; Mohd Ashhari, Zariyawati; Kharuddin, Saira (Human Resource Management Academic Research Society, 2024)
The COVID-19 pandemic has had significant global social, political and economic repercussions, with small and medium enterprises (SMEs) being particularly affected. SMEs in Saudi Arabia are trying to demolish barriers in traditional sectors with proven resilience. SMEs are a cornerstone for Arab economies. According to the General Authority, also known as Monsha’at, SMEs represent 90% of all businesses in the Kingdom but are still excluded from major industries. Even after COVID-19 pandemic, a drastic change has been noticed in the number of SMEs in Saudi Arabia, reaching 892,063 in June 2022. This study examines the impact of the COVID-19 pandemic on the financial performance of SMEs in Saudi. Knowingly, that SMEs contribute to the growth of Saudi Arabia, it is good to know how the internal challenges of SMEs can affect financial performance. Furthermore, this study explain the important of business support in SMEs operations. Arabia and its consequences on the local market and workforce. Human capital is a competitive edge for organisations investing in it and is a crucial stage for SMEs to invest an ample amount in skill development instead of allocating a major part of their financing to technological adoption. This study employed a quantitative approach by distributing adapted questionnaires to SMEs across various sectors. A total of 390 questionnaires were collected from SMEs owners and managers representing all states in Saudi Arabia via Google Forms, where all questions are mandatory to answer. The resource-based view theory was used to support proposed relationships and hypotheses. This study employed SPSS and AMOS for analysing data. Exploratory factor analysis was used, eliminating four questions as they did not fulfil the requirement for acceptance. Structural Equation Modelling was used to present the data in graphical form and show the values of estimates. Internal factors dimension values were taken as cumulative. The findings of this study show that the first two alternative hypotheses were accepted and that the moderation of business support among internal challenges and financial performance is also proved. For example, a lack of experienced workers or leakage of resources can affect SMEs' performance. SMEs in Saudi Arabia faced difficulties in recovering from the damage caused by COVID-19. Finally, the findings of this study reveal that SMEs require additional business support, both financial and non-financial, to overcome challenges and enhance their performance.